2012
DOI: 10.5012/bkcs.2012.33.11.3749
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Narrow Pore Size Distribution on Carbon Dioxide Capture of Nanoporous Carbons

Abstract: Nanoporous carbons with a high specific surface area were prepared directly from thermoplastic acrylic resin as carbon precursor and MgO powder as template by carbonization over the temperature range, 500-1000 °C. The effect of the carbonization temperature on the pore structure and CO 2 adsorption capacity of the obtained porous carbon was examined. The textural properties and morphology of the porous carbon materials were analyzed by N 2 /−196 °C and CO 2 /0 °C adsorption/desorption isotherms, SEM and TEM. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…The maximum CO 2 adsorption capacity obtained is higher than that of some of the carbon based adsorbents such as activated nanocarbon bers and carbon spheres reported in the literature. [32][33][34] A comparison of the CO 2 adsorption of STC and other carbons with similar pore properties is listed in Table S1 of the ESI. † High pressure gas adsorption measurements for CO 2 were performed on STC using a high pressure volumetric gas analyzer and the adsorption isotherms are given in Fig.…”
Section: Co 2 Adsorption Evaluation Of Cotton-stcmentioning
confidence: 99%
“…The maximum CO 2 adsorption capacity obtained is higher than that of some of the carbon based adsorbents such as activated nanocarbon bers and carbon spheres reported in the literature. [32][33][34] A comparison of the CO 2 adsorption of STC and other carbons with similar pore properties is listed in Table S1 of the ESI. † High pressure gas adsorption measurements for CO 2 were performed on STC using a high pressure volumetric gas analyzer and the adsorption isotherms are given in Fig.…”
Section: Co 2 Adsorption Evaluation Of Cotton-stcmentioning
confidence: 99%
“…The affinity between the CO 2 and carbon membrane pore wall suggested that kinetic diameter was not the sole factor in determining the magnitude of the gas permeabilities, but also the affinity of the diffusing molecules towards the carbon membrane pore wall [10]. This affinity is originated from the Volume 1 • Issue 1 • 1000103 Int J Petrochem Res.…”
Section: Resultsmentioning
confidence: 99%
“…The carbonization temperature is 900°C-1,000°C for thermosetting polymers. 1 Inside the base of the lower denture, on the right side, the temperature was near 900°C, where was missing the thermosetting polymer structure of the rehabilitation (Figure 6). The left side of the rehabilitation structure was intact; it was not carbonized because the fire intensity was less than the thermosetting polymer carbonization temperature.…”
Section: Examination Of the Teethmentioning
confidence: 99%
“…The primary purpose of a body fire investigation is to establish the origin of the fire, the temperature of the fire, the body's position, and determine the likely cause; and thus, conclude whether the death was accidental, natural, or deliberate. 1,2 The field of forensic dentistry, or the more professional term, forensic odontology, is the application of dentistry to the law. Forensic dentistry is now an integral part of criminal investigations.…”
Section: Introductionmentioning
confidence: 99%